Evaluation of portal vein velocity in non alcoholic fatty liver disease by Doppler ultrasound (Nepal Medical College Journal, 2022)
Nonalcoholic fatty liver disease is being increasingly recognized as one of the major causes of chronic liver disease. It is associated with various metabolic condition including obesity and diabetes. As the incidence of diabetes and obesity is increasing every day due to change in lifestyle, the incidence of nonalcoholic fatty liver disease is also increasing and so does its related chronic liver disease. Doppler ultrasound is easily available, noninvasive modality to see the hemodynamics of portal vein in various diffuse liver diseases. Our objective in our study is to show the correlation between the nonalcoholic fatty liver disease and Doppler findings of portal vein. The study was conducted in Department of Radiology of College of medical sciences, Bharatpur. Total 70 participants with in group of 30-60 years were included in our study (50 patients with fatty liver disease and 20 with normal liver parenchyma). All ultrasound examination performed with the Toshiba Aplio 500 with convex array deep probe of frequency 3.5MHZ. Prospective cross-sectional study was conducted over the period of one year between September 2020 to August 2021. The mean age of our patients with fatty liver was 42.1 ± 8.4 years, mean BMI was 30.6 ± 3.6 similarly mean V_min and V_max of portal vein is 20.0 ± 7.7cm/s and 24.6 ± 7.4cm/s respectively. Same way the control group without fatty liver had 40.6 ± 9.7 years mean age, 23.55 ± 4.8cm/s mean BMI, 30.05 ± 5.1cm/s mean V_min and 34 ± 5.0cm/s mean V_max. There is statistically significant difference of mean BMI (p